Tuning of the magnetostrictive properties of cobalt ferrite by forced distribution of substituted divalent metal ions at different crystallographic sites - Anantharamaiah, P. N.; Joy, P. A. (Journal of Applied Physics, 2017)
Comparative studies have been made to understand the role of different crystallographic site preferences of the substituted non-magnetic divalent metal ions in the magnetostrictive properties of cobalt ferrite, by substitution of Zn2+ and/or Mg2+ for Fe3+ in CoMgxFe2-xO4, CoZnxFe2-xO4, and CoMgx/2Znx/2Fe2-xO4 (0.0 <= x <= 0.2). Detailed Raman spectral and magnetic characterizations are made to extract the information on the tetrahedral/octahedral site preferences of Zn and Mg in the spinel lattice of cobalt ferrite. The structural, microstructural, magnetic, Raman spectral, and magnetostrictive parameters of the studied compositions show distinguishable variations for x< 0.1 and x >= 0.1. Co-substitution of a small amount of Mg and Zn for Fe in CoMgx/2Znx/2Fe2-xO4 (x < 0.1) showed relatively larger strain sensitivity, [d lambda/dH](max) (-2.6 x 10(-9) mA(-1) for x = 0.05), higher than that for the Mg-substituted samples (-2.05 x 10(-9) mA(-1) for x = 0.05) and comparable to that for the Zn-substituted samples (-2.47 x 10(-9) mA(-1) for x = 0.05), without much drop in the maximum value of magnetostriction, lambda(max) (-189 ppm for x = 0.05) compared to that for the unsubstituted counterpart (-221 ppm). The results show that it is possible to obtain high strain sensitivity (at fields < 50 kA/m), along with high magnetostriction strain at low magnetic fields (similar to 250 kA/m), by tuning the distribution of the substituted cations in the tetrahedral and octahedral sites of the cobalt ferrite lattice. Published by AIP Publishing.